Exploring algae and cyanobacteria as a promising Q6 natural source of antiviral drug against SARS-CoV-2 (2020)
The present outburst of coronavirus-associated (SARS-CoV-2) acute respiratory disease coronavirus disease 19 (COVID-19) in December 2019 in Wuhan, China is the third recognised spill over due to the zoonotic transmission. SARS-CoVs are about 29.7 kb positive, single stranded (ss) RNA viruses that are considered as zoonotic pathogens, bat being their natural reservoirs and also shows transmission within humans. The rapidly increasing COVID-19 cases and need of best and efficient drug/vaccine/strategy to counteract the virus entry and its pathogenesis has made it a Herculean challenge for scientists. Synthetic drugs associated complications has attracted scientific attention for natural product-based drugs. Chemo-diversity of algae and cyanobacteria offers a novel approach and can be recognized as a relevant source for developing a future natural “antiviral drug”. The aim of this review is to highlight important features of SARS-CoV-2/COVID-19 and the antiviral compounds recognized in algae and cyanobacteria, with their mechanisms of actions. Algae possess both immunity improving capacity and suppresses many viruses. Thus, they can be recommended as a preventive and curative remedy against SARS-CoV-2.